2012
DOI: 10.5380/tes.v5i1.25458
|View full text |Cite
|
Sign up to set email alerts
|

Qualificação para as atividades do turismo: Perfil profissional de trabalhadores, proprietários e gestores de empresas de alimentação fora do lar na Região Litorânea Central do Estado de Santa Catarina (Brasil)

Abstract: RESUMO -A pesquisa foi realizada entre novembro de 2008 e março de 2009 a fim de levantar o perfil profissional de trabalhadores, proprietários e gestores de estabelecimentos de alimentação fora do lar em municípios da Região Litorânea Central do Estado de Santa Catarina. Metodologia: A pesquisa foi realizada em sete municípios: Florianópolis, São José, Governador Celso Ramos, Biguaçu, Palhoça, Paulo Lopes e Garopaba. Foram respondidos 1.516 questionários: 1.110 por funcionários (73,22%) e 406 por gestores ou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Besides the diversity of the food offering, it was observed that most of the restaurants have more than one Applied Tourism ISSN: 2448-3524 https://siaiap32.univali.br/seer/index.php/ijth/index long working hours (Assunção et al, 2010). Also, Rocha and Amaral (2012), in their study on the profile of workers in the out-of-home food sector of the Central Coastal Region of Santa Catarina, observed that the employees had low levels of education, with 63% not having completed high school.…”
Section: Profile Of Restaurants Around the Reta Da Base Aérea De Sant...mentioning
confidence: 99%
“…Besides the diversity of the food offering, it was observed that most of the restaurants have more than one Applied Tourism ISSN: 2448-3524 https://siaiap32.univali.br/seer/index.php/ijth/index long working hours (Assunção et al, 2010). Also, Rocha and Amaral (2012), in their study on the profile of workers in the out-of-home food sector of the Central Coastal Region of Santa Catarina, observed that the employees had low levels of education, with 63% not having completed high school.…”
Section: Profile Of Restaurants Around the Reta Da Base Aérea De Sant...mentioning
confidence: 99%
“…Management and tourism make up the fourth line of studies about eating out in Brazil. Discussion on the issue is still quite dispersed including sociological approaches, as in Silva (2011), Gimenes (2011), and Soares (2014, with a growing corpus of empirical work on areas with high touristic potential, such as coastal regions (Rocha and Amaral, 2012), or which seek to redeem or value historical and cultural aspects of a given region (Grechinsk and Cardozo, 2008). However, these are usually focused on exploiting the economic potential of a particular place through its food, by attracting visitors across Brazil and/or from other countries, highlighting culture and landscape.…”
Section: Introductionmentioning
confidence: 99%